The direct exploitation in the mangrove ecosystem in Central Java and the land use in its surrounding; degradation and its restoration effort - AHMAD DWI SETYAWAN; KUSUMO WINARNO (Biodiversitas Journal of Biological Diversity, 2006)
The aims of the research were to find out (i) the direct exploitation in the mangrove ecosystem, (ii) the land use in its surrounding, and (iii) the restoration activities in the mangrove ecosystem in northern coast and southern coast of Central Java Province. This was descriptive research that was done qualitatively, in July until December 2003, at 20 sites of mangrove habitat. The data was collected in field surveys, in-depth interview to local people and/or local government, and examination of topographic maps of Java (1963-1965) and digital satellite image of Landsat 7 TM (July-September 2001). The result indicated that the direct exploitation in the mangrove ecosystem included fishery, forestry, food stuff, cattle woof, medicinal stuff, industrial material, and also tourism and education. The land use around mangrove ecosystem included fishery/embankment, agriculture, and the area of developing and building. The anthropogenic activities had been degraded mangrove ecosystem, it was called for restoration. The mangrove restoration had been done success in Pasar Banggi, but it failed in Cakrayasan and Lukulo.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: direct use, land use, mangrove ecosystem, degradation, restoration, Central Java Province.